2021
DOI: 10.1126/scitranslmed.abh2624
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon autoantibodies are associated with systemic immune alterations in patients with COVID-19

Abstract: Neutralizing autoantibodies against type I interferons (IFNs) have been found in some patients with critical coronavirus disease 2019 (COVID-19), the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, the prevalence of these antibodies, their longitudinal dynamics across the disease severity scale, and their functional effects on circulating leukocytes remain unknown. Here, in 284 patients with COVID-19, we found type I IFN-specific autoantibodies in peripheral blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
171
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(203 citation statements)
references
References 59 publications
(86 reference statements)
15
171
4
Order By: Relevance
“…Neutralizing autoantibodies against type-I IFNs, particularly to the 13 IFN-α subtypes and IFN-ω, were recently identified in ∼10% of patients suffering from critical COVID-19 pneumonia (92) and were shown to delay SARS-CoV-2 clearance (93). This observation was confirmed in independent patient cohorts (94)(95)(96). In addition, inborn errors of type-I IFN immunity were reported in some -but not all-examined cohorts of patients with life-threatening COVID-19 (97)(98)(99).…”
Section: Covid-19 Infection and Vaccination In Apeced Patientsmentioning
confidence: 74%
“…Neutralizing autoantibodies against type-I IFNs, particularly to the 13 IFN-α subtypes and IFN-ω, were recently identified in ∼10% of patients suffering from critical COVID-19 pneumonia (92) and were shown to delay SARS-CoV-2 clearance (93). This observation was confirmed in independent patient cohorts (94)(95)(96). In addition, inborn errors of type-I IFN immunity were reported in some -but not all-examined cohorts of patients with life-threatening COVID-19 (97)(98)(99).…”
Section: Covid-19 Infection and Vaccination In Apeced Patientsmentioning
confidence: 74%
“…It was indeed notably constituted in order to assess associations between treatments and outcomes like need of ventilation mechanic and mortality [16]. Overall, severity of patients studied here was potentially lower than that of patients hospitalized in Intensive Care Units [5,6,[9][10][11]14].…”
Section: Discussionmentioning
confidence: 99%
“…They were not detected in patients with asymptomatic or mild SARS-CoV-2 infection. They were also shown to block the anti viral activity of correspondent type I IFNs against SARS-CoV-2 in vitro and in vivo [5].These findings were replicated in other cohorts in Amsterdam, Madrid, San Francisco, Lyon and New Haven [6][7][8][9][10][11][12][13] Recently, auto-Abs neutralizing lower, more physiological concentrations of type I IFNs were detected in 15 to 20% of patients with critical COVID-19, notably in more than 20% of critical patients over 80 years of age. When also considering auto-Abs to IFN-beta, they were present in about 20% of deceased patients across all ages [14].…”
Section: Introductionmentioning
confidence: 89%
“…Interindividual clinical variability in the course of SARS-CoV-2 infection is huge, ranging from silent infection to fatal COVID-19 ( 1 ). We have reported that life-threatening COVID-19 pneumonia can be caused in about 20% of cases by rare inborn errors of Toll-like receptor (TLR)3-, TLR7-, or IRF7-dependent type I interferon (IFN) immunity ( 2 , 3 ), or by the presence of autoantibodies (auto-Abs) neutralizing IFN-α2 or IFN-ω, or more rarely IFN-β ( 4 16 ). These auto-Abs were long known to exist but were previously thought to be clinically silent.…”
mentioning
confidence: 99%